The Role of microRNAs in Osteoporosis Diagnostics - Hackl, Matthias; Semmelrock, Elisabeth; Grillari, Johannes (Osteologie, 2021)
MicroRNAs (miRNAs) are short (18–24 nucleotides) non-coding RNA sequences that regulate gene expression via binding of messenger RNA. It is estimated that miRNAs co-regulate the expression of more than 70% of all human genes, many of which fulfil important roles in bone metabolism and muscle function. In-vitro and in-vivo experiments have shown that the targeted loss of miRNAs in distinct bone cell types (osteoblasts and osteoclasts) results in altered bone mass and bone architecture. These results emphasize the biological relevance of miRNAs for bone health.MiRNAs are not only considered as novel bone biomarkers because of their biological importance to bone metabolism, but also on the basis of other favorable properties: 1) Secretion of miRNAs from cells enables “minimally invasive” detection in biological fluids such as serum. 2) High stability of miRNAs in serum enables the retrospective analysis of frozen blood specimens. 3) Quantification of miRNAs in the serum is based on the RT-PCR - a robust method that is considered as the gold standard for the analysis of nucleic acids in clinical diagnostics.With regard to osteoporosis, it has been shown that many of the known risk factors are characterized by distinct miRNA profiles in the affected tissues: i) age-related loss of bone mass, ii) sarcopenia, iii) changes in estrogen metabolism and related changes Loss of bone mass, and iv) diabetes. Therefore, numerous studies in recent years have dealt with the characterization of miRNAs in the serum of osteoporosis patients and healthy controls, and were able to identify recurring miRNA patterns that are characteristic of osteoporosis. These novel biomarkers have great potential for the diagnosis and prognosis of osteoporosis and its clinical outcomes.The aim of this article is to give a summary of the current state of knowledge on the research and application of miRNA biomarkers in osteoporosis.MikroRNAs (miRNAs) sind kurze (18–24 Nukleotide) RNA Moleküle, welche über die Bindung an Botenstoff-RNA (messengerRNA) die Genexpression regulieren. Derzeit sind circa 2500 humane miRNAs annotiert. Circa 70% aller humanen Gene werden durch diese miRNAs co-reguliert, darunter viele Gene mit wesentlichen Funktionen für den Knochenstoffwechsel und die Muskelfunktion. Experimente in der Petrischale und im Tiermodell konnten zeigen, dass der zielgerichtete Verlust von miRNAs in Zelltypen des Knochens (Osteoblasten und Osteoklasten) zu starken Veränderungen der Knochenstruktur führen, woraus sich eine große Relevanz von miRNAs für die Knochengesundheit ableiten lässt.Als Knochenbiomarker zeichnen sich miRNAs aber nicht nur wegen ihrer biologischen Funktionen im Knochenstoffwechsel aus, sondern auch auf Basis weiterer günstiger Eigenschaften: 1) Die Sekretion von miRNAs aus Zellen ermöglicht eine „minimal-invasive“ Detektion in Bioflüssigkeiten wie zum Beispiel Serum. 2) Die hohe Stabilität von miRNAs im Serum vereinfacht retrospektive Analysen von gefrorenen Blutproben. 3) Die Quantifizierung von miRNAs im Serum erfolgt auf Basis der RT-PCR – eine robuste Methode die als Goldstandard für die Analytik von Nukleinsäuren in der klinischen Diagnostik gilt.In Bezug auf die Osteoporose konnte gezeigt werden, dass viele der bekannten Risikofaktoren zu Veränderungen von miRNA Profilen in den betroffenen Geweben führen: i) Altersbedingter Verlust an Knochenmasse, ii) Sarkopenie, iii) Veränderungen im Östrogenstoffwechsel und daraus bedingter Verlust an Knochenmasse, und iv) Diabetes. In weiterer Folge haben sich in den vergangenen Jahren zahlreiche Studien mit der Charakterisierung von miRNAs im Serum von Osteoporosepatient*innen und gesunden Kontrollen auseinandergesetzt, und konnten miRNA Muster identifizieren, welche mit niedriger Knochendichte und erhöhtem Frakturrisiko assoziiert sind. Diese neuartigen Biomarker haben großes Potenzial für die Diagnose und Prognose der Osteoporose, insbesondere der klinischen Konsequenz in Form von Fragilitätsfrakturen.Dieser Artikel fasst den derzeitigen Wissenstand in Bezug auf die Erforschung und Anwendung von miRNAs als Biomarker für Osteoporose zusammen.
Keywords: microRNA; biomarker; osteoporosis; fragility fracture; osteomiR